2022
DOI: 10.2174/1574888x16666210804112741
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells in Veterinary Regenerative Therapy: Basic Physiology and Clinical Applications

Abstract: Background: The consistent, self-renewal capability and wide-ranging differentiation potential during specific physiologic conditions mark stem cells as a novel candidate not only for biomedical research and regenerative therapy but also as an alternative source in research related to life sciences. This vital and distinct characteristic of stem cells, enable them to offer unprecedented hope in treating many diseases and disorders, which are otherwise difficult to treat. Several efforts are still being undert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Recently, tissue engineering approaches have attracted attention for tissue repair. Among the approaches, the use of mesenchymal stem cell-based therapy has increased, since it is a promising approach for tissue repair and regeneration including tendinopathy and desmitis [ 1 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, tissue engineering approaches have attracted attention for tissue repair. Among the approaches, the use of mesenchymal stem cell-based therapy has increased, since it is a promising approach for tissue repair and regeneration including tendinopathy and desmitis [ 1 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that MSCs can self-renew, migrate to injury sites (homing), perform multilineage differentiation, and secrete bioactive factors, thus, increasing proliferation and migration of tendon stem/progenitor cells via paracrine signaling and increasing the regeneration ability of tissues with poor aptitude [ 1 , 3 , 4 , 5 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stem cell therapies for wound healing have depended on adult MSCs 3,4 . The therapeutic effects of MSCs are attributed to their biological properties, such as immunomodulatory ability, anti‐inflammatory and antimicrobial properties and many more 5 . Bone marrow is a common source for MSCs, but the drawback is its invasive and painful collection procedure and the significantly lower proportion of MSCs obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Based on most recent studies, the prospect of cellular regeneration is found in the paracrine activity of cAD-MSCs, called secretome ( 10–12 ). The secretome encompasses soluble factors, including cytokines, growth factors, morphogens, chemokines, and non-soluble factors, known as extracellular vesicles containing proteins, lipids and RNAs ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…From the current point of view, cAD-MSCs secretome provides several advantages over cAD-MSCs cell therapy, such as a lower risk of thrombosis and tumor formation and easier manufacturing, handling, and storage. Furthermore, secretome could be mass-produced under controlled conditions, tailored for therapeutic effects, and stored for immediate use in acute conditions without the need for a donor or time-consuming cell expansion ( 10 , 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%